Fantasy Themes of Marine Retiree Group - Puspita, Virienia (Bina Nusantara University, 2017)
The research applied symbolic convergence theory as the main theories, with the subjective- interpretive paradigm. Through a qualitative approach, this study was conducted by using fantasy themes analysis. The subjects of this study were members of Marines retiree who lives in Tanah Baru and Rangkapan Jaya Baru, Depok. The object of this research was the aspect of communication in the form of verbal and nonverbal symbols of Marine retiree group members in expressing their fantasy themes. Thirteen informants were chosen as the sample with purposive and snowball sampling techniques. This study aimed to find and identify the fantasy themes of Marine retiree group through elements of setting, character, and action. The results show that the story of Marine retiree group is a bridge that connects the experience of the retired members of the Marines in the events of the past with the present time.